Protocolo de mantenimiento electromecánico a equipos de jardinería de la empresa Suministros Gutiérrez S.A (2022)
This research work was carried out with the purpose of implementing an electromechanical maintenance protocol for pruning equipment, used by the contractor company Gutiérrez S.A for operation in the green areas of the TIBÚ field, operations management of Ecopetrol S.A.; The company currently has a group of technicians for the maintenance of the equipment used in this work, but an operation strategy is required to optimize resources. The investigation carried out of the technical information of the equipment and the maintenance activity of the green areas allowed to visualize shortcomings in the operation and maintenance of these. These shortcomings can be improved by applying protocols that include preventive maintenance. In the process of designing the protocol, preventive maintenance was included with a route and a very simple application plan through a series of formats derived from the designed protocol, which must be completed by the operators at the beginning and at the end of the work. pruning, obtaining information on the status of each equipment at the beginning and end of its operation; This information is the main input for the maintenance department. Finally, the protocol indicates some recommendations based on the ISO 55001 standard that deals with the administration of assets and the proper use of the devices used for the protection and safety of the personnel that operates the pruning machinery.